1968
DOI: 10.1099/00221287-53-3-383
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Germination of Bacterial Spores by Analogues of D-Alanine

Abstract: SUMMARYL-Alanine-initiated germination of spores of Bacillus cereus was potentiated by the following structural analogues of alanine : 0-carbamyh-serhe (OCDS), D-cycloserine (DCS), P-alanylhydroxamic acid (PAHA) and glycyl hydroxamic acid (GHA) ; but not by D-a-alanyl-hydroxamic acid (DAHA). Potentiation of germination resulted from inhibition of alanine racemase in the spores with consequent suppression of the formation of D-alanine, an inhibitor of L-alanine-initiated germination. OCDS was the most effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

1968
1968
1993
1993

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…However, this support rested on the assumption that similar mechanisms were involved in the observed stimulatory effects, and this appeared not to be true, at least in the case of hydroxylamine. It was reported elsewhere that, by inhibiting alanine racemase in B. cereus spores, hydroxylamine could relieve an auto-inhibition of germination arising from isomerization of L-alanine (Jones & Gould, 1968). Experiments subsequent to the above comparisons of amines (to be published elsewhere) revealed that inhibition of alanine racemase could account for almost all of the stimulatory effect of hydroxylamine (Fig.…”
Section: I-mentioning
confidence: 71%
“…However, this support rested on the assumption that similar mechanisms were involved in the observed stimulatory effects, and this appeared not to be true, at least in the case of hydroxylamine. It was reported elsewhere that, by inhibiting alanine racemase in B. cereus spores, hydroxylamine could relieve an auto-inhibition of germination arising from isomerization of L-alanine (Jones & Gould, 1968). Experiments subsequent to the above comparisons of amines (to be published elsewhere) revealed that inhibition of alanine racemase could account for almost all of the stimulatory effect of hydroxylamine (Fig.…”
Section: I-mentioning
confidence: 71%
“…studied. OCDS is a powerful inhibitor of spore alanine racemase, and the observed potentiation of germination has been shown to be due to prevention by OCDS of the formation of D-alanine catalysed by the racemase enzyme (Gould, 1966;Jones & Gould, 1968). Nevertheless, even using organisms whose spores are more easily germinated than those of most bacteria, in rich media to which had been added the most effective germinants we know, germination still levelled off to leave a population of surviving spores only 10-to 100-fold smaller than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Jones and Gould [5] and Yousten [22] reported that inosine might enhance the activity of alanine racemase. From this point of view, it is possible that the inhibition of subsequent germination of the spores preincubated with inosine may be due to the effect of D-alanine which was converted from L-alanine by active alanine racemase.…”
Section: Discussionmentioning
confidence: 99%
“…Purine ribosides are also effective germinants for various species of spores [2,5,6,9]. In particular, it was pointed out that inosine greatly stimulated germination in the presence of L-alanine [1,5,14,22].…”
mentioning
confidence: 99%
See 1 more Smart Citation